PENERIMAAN SENSORI ROTI JAGUNG YANG DIFORTIFIKASI TEPUNG DAUN KELOR (Moringa oleifera) - Maria susana Medho; Endeyani V. Mohamad (Partner, 2021)
This study aims at evaluating the level of preference for Moringa cornbread. The research was conducted with variations in the concentration of Moringa leaf flour (KK): KK1 = 1%; KK2 = 3%; KK3 = 5%; KK4 = 7%. The parameters analyzed included the level of preference for color, texture, taste, aroma. The results showed that the hedonic value of color, texture, taste, and aroma was highest in 5% Moringa leaf flour and was not significantly different from the addition of 3% Moringa leaf flour, meaning that the panelists liked the bright green color, soft texture, sweet and not bitter taste with a little unpleasant aroma The lowest hedonic value was the addition of 7% Moringa leaf flour, which means that the panelist didn’t like dark green, the texture was rather hard, rough, inelastic, bitter taste and a dry impression wrinkled in the mouth and smelled unpleasant.  Key Words:  Reception, Sensoric, Bread, Corn, Moringa